Studi Semiotika Charles Sanders Peirce pada Kompas TV dalam Pemberitaan Efisiensi Dana Kabinet Prabowo - Audina, Diva Nadiastiti (Jurnal Audiens, 2025)
This study analyzes the representation of the budget efficiency policy in the Prabowo-Gibran cabinet within Kompas TV news reports using Charles Sanders Peirce's semiotic approach. The research aims to uncover hidden meanings behind visual, linguistic, and symbolic signs employed by the media in framing the budget policy issue. Peirce's triadic concept—icon, index, and symbol—is applied to examine the relationship between signs and the construction of meaning conveyed by the media. The research method used is content analysis based on literature study of three news articles published by Kompas TV in February 2025. The findings show that Kompas TV represents the budget efficiency policy in a contradictory manner, with two news articles highlighting the negative impacts of the policy on marginalized communities by emphasizing the discourse of unequal budget distribution, while one article portrays the policy as the government's effort to maintain public welfare. These findings indicate that the media not only act as information conveyors but also as actors shaping public opinion through the construction of meanings that are persuasive and ideological. This study contributes to media studies by illustrating how semiotic practices are used to reinforce critical discourse on public policy.